The Success of Servant Leadership and Empowerment on the Quality of Work Life at PT Reasuransi Indonesia Utama (Persero) - Teti Rohayati (Budapest International Research and Critics University, 2022)
This This study aims to obtain information and analyze the direct and indirect effect of servanteadership, empowerment and quality of work life of employees. The research uses a quantitive approach with survey methods. Data collection using a questionnaire and a sample of 137 people, using proportionate stratified random sampling with Structural Equation Modeling (SEM) analysis using SmartPLS 3.0 based on covariance. The results showed that: (1) servant leadership has airect effect on empowerment, (2) servant leadership has a direct effect on the quality of employee work life, (3) empowerment has a direct effect on the quality of employee work life (4) the indirect influence of servant leadership on quality. In addition, the emphasis in this study is that to improve the quality of employee’s work life is to pay attention to service leadership either directly or indirectly through empowerment.